Environmental effects of ozone depletion, UV radiation and interactions with climate change: UNEP Environmental Effects Assessment Panel, update 2017. Issue 2 (6th February 2018) - Bais, A. F.; Lucas, R. M.; Bornman, J. F.; Williamson, C. E.; Sulzberger, B.; Austin, A. T.; Wilson, S. R.; Andrady, A. L.; Bernhard, G.; McKenzie, R. L.; Aucamp, P. J.; Madronich, S.; et al.
Abstract : The present 2017 Update Report assesses some of the highlights about the interactive nature of the direct and indirect effects of UV radiation, atmospheric processes, and climate change. Abstract : The Environmental Effects Assessment Panel (EEAP) is one of three Panels of experts that inform the Parties to the Montreal Protocol. The EEAP focuses on the effects of UV radiation on human health, terrestrial and aquatic ecosystems, air quality, and materials, as well as on the interactive effects of UV radiation and global climate change. When considering the effects of climate change, it has become clear that processes resulting in changes in stratospheric ozone are more complex than previously held. Because of the Montreal Protocol, there are now indications of the beginnings of a recovery of stratospheric ozone, although the time required to reach levels like those before the 1960s is still uncertain, particularly as the effects of stratospheric ozone on climate change and vice versa, are not yet fully understood. Some regions will likely receive enhanced levels of UV radiation, while other areas will likely experience a reduction in UV radiation as ozone- and climate-driven changes affect the amounts of UV radiation reaching the Earth's surface. Like the other Panels, the EEAP produces detailed Quadrennial Reports every four years; the most recent was published as a series of seven papers in 2015 ( Photochem. Photobiol. Sci., 2015, 14, 1–184). In the years in between, the EEAP produces less detailed and shorter Update Reports of recent and relevant scientific findings. The most recent of these was for 2016 ( Photochem. Photobiol. Sci ., 2017, 16, 107–145). The present 2017 Update Report assesses some of the highlights and new insights about the interactive nature of the direct and indirect effects of UV radiation, atmospheric processes, and climate change. A full 2018 Quadrennial Assessment, will be made available in 2018/2019.